Koreas Inpayments and Outpayments with the Rest of the World: Is There Room for Currency Manipulation? - Bahmani-Oskooee, Mohsen; Zhang, Ruixin (Asian Economic and Financial Review, 2015)
In estimating the well-known Marshall-Lerner condition, researchers have used trade volume data between one country and rest of the world. To reduce aggregation bias in these studies, it is proposed to use trade data at commodity level. However, due to lack of import and export prices to obtain trade volume at commodity level, researchers have used trade values instead. These value models are used to assess the direct impact of currency depreciation on inpayments and outpayments of an industry. In this paper we assess the sensitivity of inpayments and outayments of 148 Korean industries that trade with the rest of the world. We were able to identify 20 Korean exporting industries and 38 importing industries that will benefit from won depreciation in the long run.